STRATEGY E-LEARNING FACILITATES STUDENT CONCEPT UNDERSTANDING ON HEAT MATERIAL AND ITS TRANSFER DURING THE COVID-19 PANDEMIC - Achmad Fathoni Rodli; Ratih Ratih; Intan Kusumawati; Emi Sulistri (STKIP Singkawang, 2022)
This study aims to analyze e-learning strategies to facilitate students' understanding of the concept of heat and its transfer in class XI during the Covid-19 pandemic. This research method uses a qualitative descriptive method. The subjects in this study were students of SMA Negeri 2 Teluk Keramat class XI MIPA 2, totaling 28 people. This research instrument uses interview guidelines for teachers and students, and documentation of the results of students' conceptual understanding tests. From this research, it can be concluded that the e-learning strategy that has been used does not make it easier for students to understand the concept well. This is evidenced from the results of teacher and student interviews and the results of understanding the concepts obtained are low where there are 61% of students at the level of concept understanding and it is also proven based on each indicator, namely interpreting 35.71%, exemplifying 83.93%, classifying 85.71%, summarized 42.86%, concluded 0.00%, compared 62.50%, and explained 60.71%.